Dreaming Faith into Being: Indigenous Evangelicals and co-acted experiences of the divine. - Minna Opas (Finland, 2022)
This article examines the role of socio-moral space in people’s experiences of divine presence. More specifically, it addresses the questions of how social others influence people’s experiences of God and Satan among the indigenous evangelical Yine people of Peruvian Amazonia, and the consequences these interactions have for the individual believer and the collectivity. For the Yine dreams are a privileged site of human encounter with other-than-human beings, and they also feature centrally in their Christian lives. It is in dreams that they interact with angels and sometimes with the devil. By examining Yine evangelical dreams as mimetic points of encounter involving not only the dreamer but also transcendent beings and fellow believers as active agents, the article shows that Yine experiences of God’s presence cannot be conceptualised as an individual matter, but are highly dependent on the social other: they come to be as co-acted experiences of the divine.